Standards of Beauty: The Impact of Mannequins in the Retail Context - Argo, Jennifer J; Dahl, Darren W (Journal of Consumer Research, 2018)
Abstract Across six studies, a female mannequin is demonstrated to have negative implications for both male and female consumers low in appearance self-esteem. In particular, consumers who are lower in appearance self-esteem evaluate a product displayed by a mannequin more negatively as compared with consumers higher in appearance self-esteem. As mannequins signal the normative standard of beauty and consumers with low self-esteem in regard to their appearance believe they fail to meet this standard, these consumers become threatened by the beauty standard when exposed to a mannequin and in response denigrate the product the mannequin is displaying. We provide evidence for the underlying process in three ways: 1) through the finding that the effect for male and female consumers with low appearance self-esteem arises only when the mannequin is displaying an appearance-related product, 2) through mediation analysis demonstrating that the mannequin conveys society’s standard of beauty and that this negatively impacts product evaluations, and 3) through mitigation of the effect by removing the presence of threat via a self-affirmation task or decreasing the mannequin’s beauty (e.g., marking its face, removing its hair, or removing its head). Multiple avenues for future research are forwarded.